Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1289/ehp.96104394
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide appliers, biocides, and birth defects in rural Minnesota.

Abstract: Earlier studies by our group suggested the possibility that offspring of pesticide appliers might have increased risks of birth anomalies. To evaluate this hypothesis, 935 births to 34,772 state-licensed, private pesticide appliers in Minnesota occurring between 1989 and 1992 were linked to the Minnesota state birth registry containing 210,723 live births in this timeframe. The birth defect rate for all birth anomalies was significantly increased in children born to private appliers. Specific birth defect cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(72 citation statements)
references
References 28 publications
3
68
0
1
Order By: Relevance
“…A similar tendency was already reported [3,5]. Children conceived in the spring, when pesticides are used, are at greater risk for birth defects [6].…”
supporting
confidence: 79%
“…A similar tendency was already reported [3,5]. Children conceived in the spring, when pesticides are used, are at greater risk for birth defects [6].…”
supporting
confidence: 79%
“…Long run health impacts include cancer, infertility, miscarriage, male sterility, birth defects, and effects on the nervous system (Moses, 1995). Farm workers are at much greater risk of toxicity due to exposure to pesticides (see Garry et al (1996), Pingali et al (1994), Crissman et al (1994, US Environmental Protection Agency (EPA) (1992) for cases and scientific evidence). People residing close to farmland can also experience pesticide related problems due to dumping of pesticide wastes, wind drafts from aerial spraying, or from the use of empty pesticide containers for drinking water storage (see Repetto and Baliga (1996), US Environmental Protection Agency (EPA) (1992) for cases and scientific evidence).…”
Section: Health Hazards Of Pesticides and Maximum Residue Standardsmentioning
confidence: 99%
“…One nested case-control study reported a moderate increase in premature births among workers in Columbian greenhouses [11]. Other studies have found an association between prenatal pesticide exposure and fetal growth delay [12][13][14]; various birth defects, including orafacial defects [15], cryptorchidism [16][17][18], musculoskeletal defects [19], limb reduction defects [20,21], and neural tube defects [20,22,23]; and childhood leukemia [24,25].…”
Section: Introductionmentioning
confidence: 99%